Triterpene from the roots of Codonopsis pilosula. - Sung et al, Tran Van (Vietnam Journal of Chemistry, 2014)
From the roots of Codonopsis pilosula (Franch) Nannf (Campanulaceae) five triterpenoids: taraxerol, taraxeryl acetate, 14-a-taraxeran-3-one and D:B-friedoolean-5-ene-3-b-ol as well as a-spinasterone were isolated. Their structures have been identified by MS, 1H-, 13C-NMR spectroscopy and comparison with reported data.